2007
DOI: 10.1177/0363546507308235
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Analysis of Ankle Instability after Tibiofibular Syndesmosis Injuries

Abstract: Both physicians and athletes should be aware of inversion instability of the ankle joint caused by tibiofibular syndesmosis injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 21 publications
4
68
0
Order By: Relevance
“…7 Some in vitro studies have found that cutting of the anterior tibiofibular ligament or interosseous membrane resulted in an increase in the distance between the tibia and fibula, as well as an increase in talar rotation and tilt angle. 53,55 Lateral displacement of the fibula widens the distal tibiofibular joint, affecting the mortise structure, and is associated with excessive talar rotation. Previous in vivo studies have shown an increase in talar anterior translation, 6,32 inversion, 6 and internal rotation 6,31 in the ankles with CAI.…”
Section: Discussionmentioning
confidence: 99%
“…7 Some in vitro studies have found that cutting of the anterior tibiofibular ligament or interosseous membrane resulted in an increase in the distance between the tibia and fibula, as well as an increase in talar rotation and tilt angle. 53,55 Lateral displacement of the fibula widens the distal tibiofibular joint, affecting the mortise structure, and is associated with excessive talar rotation. Previous in vivo studies have shown an increase in talar anterior translation, 6,32 inversion, 6 and internal rotation 6,31 in the ankles with CAI.…”
Section: Discussionmentioning
confidence: 99%
“…The weight consisted of a water bag and a cable calibrated to apply 2.0 N·m of torque with the pulley-and-weight system. 27 The movements of the talus were measured via the magnetic tracking system while each load was applied ( Figure 1). The following angles and translation were calculated from the coordinates and the angles of the anatomical points.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the biomechanical function of the ATiFL has shown that once the ATiFL is cut, the tibia and lateral malleolus can move separately [Teramoto et al, 2008]. The distal tibiofibular syndesmosis at-taches the fibula dynamically at the tibia, which gives the fibula the possibility to perform a three-dimensional movement during physiological dorsalextension and plantarflexion of the ankle joint [Close, 1956;Reimann and Anderhuber, 1980;Peter et al, 1994;Beumer et al, 2003;Rammelt et al, 2008].…”
Section: Anatomical Complexesmentioning
confidence: 99%